Married Women in Legal Practice Agency and Norms in the Swedish Realm, 1350-1450 - Cederbom, Charlotte (Routledge Research in Gender and History, 2020)
This book describes the ways in which married women appeared in legal practice in the medieval Swedish realm 1350-1450, through both the agency of women, and through the norms that surrounded their actions. Since there were no court protocols kept, legal practice must be studied through other sources. For this book, more than 6,000 original charters have been researched, and a database of all the charters pertaining to women created. This enables new findings from an area that has previously not been studied on a larger scale, and reveals trends and tendencies regarding aspects considered central to married women's agency, such as networks, criminal liability, and procedural capacity.